Predictors of adherence to micronutrient supplementation before and during pregnancy in Vietnam - Gonzalez-Casanova, Ines; Nguyen, Phuong Hong; Young, Melissa F.; Harding, Kimberly B.; Reinhart, Gregory A.; Nguyen, Hieu; Nechitillo, Meredith; Truong, Truong V.; Pham, Hoa; Nguyen, Son; Neufeld, Lynnette M.; Martorell, Reynaldo; et al. (Springer, 2017)
Background: Poor adherence to micronutrient supplementation often limits the effectiveness of public health programs. While predictors of adherence to micronutrient supplementation during pregnancy are well documented, information on adherence to preconception supplements is scarce. The objective of this study was to describe the predictors of adherence to preconception and prenatal micronutrient supplementation among women participating in a randomized control trial in Vietnam.